The apple 14-3-3 protein MdGRF11 interacts with the BTB protein MdBT2 to regulate nitrate deficiency-induced anthocyanin accumulation. (1st February 2021) - Ren, Yi-Ran; Zhao, Qiang; Yang, Yu-Ying; Zhang, Tian-En; Wang, Xiao-Fei; You, Chun-Xiang; Hao, Yu-Jin
Abstract: Nitrogen is an important factor that affects plant anthocyanin accumulation. In apple, the nitrate-responsive BTB/TAZ protein MdBT2 negatively regulates anthocyanin biosynthesis. In this study, we found that MdBT2 undergoes posttranslational modifications in response to nitrate deficiency. Yeast two-hybrid, protein pull-down, and bimolecular fluorescence complementation (BiFC) assays showed that MdBT2 interacts with MdGRF11, a 14-3-3 protein; 14-3-3 proteins compose a family of highly conserved phosphopeptide-binding proteins involved in multiple physiological and biological processes. The interaction of MdGRF11 negatively regulated the stability of the MdBT2 protein via a 26S proteasome-dependent pathway, which increased the abundance of MdMYB1 proteins to activate the expression of anthocyanin biosynthesis-related genes. Taken together, the results demonstrate the critical role of 14-3-3 proteins in the regulation of nitrate deficiency-induced anthocyanin accumulation. Our results provide a novel avenue to elucidate the mechanism underlying the induction of anthocyanin biosynthesis in response to nitrate deficiency.